Changing drinking behaviour: the mediating effects of satisfaction on consumption experiences and readiness to change - Baird, Michael; Ouschan, Robyn (School of Marketing, Curtin Business School, 2009)
This study applies the disconfirmation of expectations paradigm to explain what makes the consumption of sin products (high risk alcohol consumption) a satisfactory or unsatisfactory experience. It further tests if it affects readiness to change behaviour. It illustrates that disconfirmation of expectations should focus on consumption outcomes as they motivate customers to consume products and services. Furthermore, both positive and negative outcome expectancies should be included. The alcohol expectancy literature offers operational definitions of positive and negative outcome expectancies. However, alcohol expectancy studies do not use the disconfirmation paradigm to explain high risk drinking behaviours, even though disconfirmation of expectations have been shown to be a better predictor of customer satisfaction and behavioural intentions than customer expectations. Data gained via convenience sampling of undergraduate students from all divisions within a large Australian University provided a usable sample size of 462. The results and analysis illustrate a very distinct separation of four positive outcome expectation factors and four negative outcome expectation factors. These findings are discussed with implications highlighted for theorists, marketers and social policy makers.